Upaya Pertolongan Pertama pada Orang yang Kecelakaan - Assyfa Ramadhina; Nadilla Indriani Nasution; Nur Habibah; Usiono Usiono (Jurnal Bintang Pendidikan Indonesia, 2025)
Victims of traffic accidents or even disasters that occur in the community can be fatal if they do not get immediate and appropriate help from the person closest to the victim. Community members need to be equipped with skills to provide first aid through bandaging and splinting of accident victims to minimize the impact of more serious health problems. Handling accident and disaster victims must be done quickly and precisely before health workers come to provide assistance to victims. The purpose of this study of First Aid Efforts on people who have accidents is to be able to provide first aid properly and correctly. The method we use in this research is a qualitative method using observation, interviews, and documentation. Thus, researchers have basic skills in first aid in accidents (P3K) which are very useful for saving victims' lives.